An Efficient Real Space Method for Orbital-Free Density-Functional Theory (Communications in Computational Physics, 2018)
We consider the Thomas-Fermi-von Weizsacker energy functional, with theWang-Teter correction, and present an efficient real space method for Orbital-Free Density Functional Theory. It is proved that the energy minimizer satisfies a second orderquasilinear elliptic equation, even at the points where the electron density vanishes.This information is used to construct an efficient energy minimization method forthe resulting constrained problem, based on the truncated Newton method for unconstrained optimization. The Wang-Teter kernel is analyzed, and its behavior in realspace at short and far distances is determined. A second order accurate discretizationof the energy is obtained using finite differences. The efficiency and accuracy of themethod is illustrated with numerical simulations in an Aluminium FCC lattice.